Clinical features, predisposing factors and radiological study of cerebral venous sinus thrombosis: experience from a tertiary care center in Southern India - T., Aneesh; Gururaj, Hemamalini; J. S., Arpitha; Rao, Anusha; Chakravarthy, Vaishnavi; Shetty, Abhiman (International Journal of Research in Medical Sciences, 2017)
Background: Cerebral venous thrombosis (CVT) is a less common cause of stroke with a wide range of clinical presentations, predisposing factors, radiological features and outcomes. A high index of suspicion is absolutely essential to diagnose cerebral venous thrombosis. In this article, we have reviewed the clinical spectrum and radiological profile of patients with cerebral venous thrombosis and attempted to identify the specific predisposing factors for developing cerebral venous thrombosis particularly in this region of India. Methods: 116 patients hospitalized from January 2015 to March 2017 with a final diagnosis of Cerebral Venous Thrombosis which was confirmed by imaging (MRI/MRV or CT angiography) were included. Patients who were initially diagnosed as CVT but imaging were not suggestive of the same were excluded. Results: The mean age of the study population was 35.21 years, with most patients aged between 21-30 years. 18.1% of the study population were puerperal women, much lower than earlier series. 54.54% of the men had a significant history of alcohol consumption and 10.34% of the non-puerperal women revealed a history of consuming oral contraceptive pills. Among men, seizures were the most common presenting symptom followed by headache. Women presented with headache followed by vomiting. Superior sagittal sinus, transverse sinus, cortical veins and sigmoid sinus involvement were quite common in comparison to the other sinuses. Conclusions: Accurate and prompt diagnosis of CVT is crucial because timely and appropriate therapy can reverse the disease process and significantly reduce the risk of acute complications and long-term sequelae. In this article, we have reviewed the epidemiology, causative factors, clinical features and as well as radiological pattern of CVT from an Indian perspective. Over the last decade, a relatively high incidence of CVT in fairly young individuals warrants further evaluation towards genetic predisposition for pro-thrombotic states particularly in this region of India.